Re-considering Asian Financial Regionalism in the 1990s - Shintaro Hamanaka (Asian Development Bank (ADB), 2009)
A common view holds that the trend toward Asian financial regionalism is a relatively new phenomenon that became significant after the Asian financial crisis of 1997/98. This paper challenges this view by exploring and analyzing financial regionalist projects in Asia throughout the 1990s. As they demonstrate, Asian countries, especially Japan, have held a strong desire to establish an Asia-only regional cooperation framework at least since the early 1990s. The basic policy stance of the United States (US), in contrast, was to participate in Asian forums and/or itself to propose and establish regional groupings with itself as a member. This competition is crucial to understanding the rise and fall of various regionalist projects. The analysis of Asian financial regionalism from the standpoint of the membership sheds new light on studies of regionalism. Among the important theoretical implications of this empirical study is that by exercising "blocking power" over a regionalist project, an outside power is not simply killing the proposal, but is participating in the proposed regional framework and seeking to influence it. Regionalism can be best understood as a project under which a relatively minor power seeks to establish a framework that excludes more influential states in order to increase its influence within the group.
hdl:11540/1796
Keywords: F15; F36; 330; Regionalism; regional cooperation; Asian Monetary Fund (AMF); Chiang Mai Initiative (CMI); membership; blocking power